Negotiating Indigenous Modernity: Kungun Ngarrindjeri Yunnan—Listen to Ngarrindjeri speak. (December 2015) - Rigney, Daryle; Bignall, Simone; Hemming, Steve
The objective of this article is to compare Indigenous and Western modernities by examining how contemporary Indigenous polities are finding inventive ways to assert their sovereignty. Our discussion presents an innovation in Indigenous governance introduced recently by the Ngarrindjeri people in Southern Australia. We explain the conditions in which Ngarrindjeri initiated their process of political reformation; we link our analysis to critiques of Western modernism and imperialism; and we then outline some key political technologies created by the Ngarrindjeri Nation to enable its successful influence in matters affecting their Country and community. We find that these resources remain firmly grounded in Ngarrindjeri ways of knowing, being and doing, yet they are expressed in a contemporary hybrid form that is accessible to non-Indigenous negotiation partners. As a consequence, they have established a modern Indigenous framework for intercultural negotiation of interests previously controlled by the South Australian state and other non-Indigenous organizations.